1993
DOI: 10.1111/j.1365-2141.1993.tb03093.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood progenitor cells mobilized by chemotherapy plus granulocyte‐colony stimulating factor accelerate both neutrophil and platelet recovery after high‐dose VP16, ifosfamide and cisplatin

Abstract: We report on the chemotherapy plus granulocyte colony-stimulating factor (G-CSF) induced mobilization of peripheral blood progenitor cells (PBPCs) and their impact on haematopoietic recovery following high-dose chemotherapy. Twenty-four patients with advanced solid tumours or lymphomas received standard-dose chemotherapy with VP16, ifosfamide and cisplatin (VIP) followed by filgrastim (G-CSF; 5 micrograms/kg s.c. daily for 14 d) for the prevention of chemotherapy induced neutropenia and for the simultaneous mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…16,19 Thus, any further acceleration induced by growth factor adminisClinical value and costs of G-CSF administration following autograft with mobilized peripheral blood protration may be difficult to assess. In addition, the speed of BM recovery may be variably influenced by other congenitor cells (PBPC) were evaluated in two sequential groups of 20 patients each, treated for lymphoid neofounding factors, such as quantity of progenitor cells reinfused, type of conditioning regimen and previous treatplasms in the period February 1993 to January 1996.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,19 Thus, any further acceleration induced by growth factor adminisClinical value and costs of G-CSF administration following autograft with mobilized peripheral blood protration may be difficult to assess. In addition, the speed of BM recovery may be variably influenced by other congenitor cells (PBPC) were evaluated in two sequential groups of 20 patients each, treated for lymphoid neofounding factors, such as quantity of progenitor cells reinfused, type of conditioning regimen and previous treatplasms in the period February 1993 to January 1996.…”
Section: Discussionmentioning
confidence: 99%
“…30,32,33 loablative regimens. [16][17][18][19]32,33 A direct correlation between the number of reinfused progenitors and speed of hematolAlternatively, the less pronounced thrombocytopenia might be correlated with better clinical conditions, resulting from ogic recovery is well known and values ranging from 2 to 5 × 10 6 CD34 + cells/kg have been proposed as the minia shorter neutropenic duration; this could favor platelet survival with improved efficacy of platelet transfusions and mum PBPC dose required to guarantee rapid and stable engraftment. 21,[33][34][35][36] In our HDS programs, a dose as high overall milder thrombocytopenia.…”
Section: Analysis Of Treatment Costs For the Post-graft Periodmentioning
confidence: 99%
“…Unseparated MNC as well as culture cells were grown in a standard methylcellulose assay as described previously. 16 Cytogenetic analysis of bone marrow Cytogenetic analysis was performed only before mobilization therapy. MNC from bone marrow aspirates were isolated by density gradient centrifugation over Ficoll-Hypaque (Pharmacia).…”
Section: Methodsmentioning
confidence: 99%
“…Although ifosfamide has previously been incorporated into chemotherapy regimens to mobilize PBPCs, [8][9][10][11][12][13][14] these studies have not been restricted to patients with breast cancer, [8][9][10][11]14 and those with breast cancer have generally been minimally pre-treated and not had metastatic or relapsed disease. 12,13 The choice of the most appropriate mobilization regimen for patients with previously treated disease is further limited by prior cyclophosphamide and/or anthracycline exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, ifosfamide can be incorporated into chemotherapy regimens to mobilize PBPCs. [8][9][10][11][12][13][14] Secondly, ifosfamide has some potential 428 advantages over cyclophosphamide. Pre-clinical studies have demonstrated that the unique structural properties of ifosfamide may have a beneficial anti-tumor activity; ifosfamide is an analogue of cyclophosphamide with translocation of a chlorethyl group which provides a more effective DNA cross-linking distance between two independent functional alkylating moieties.…”
mentioning
confidence: 99%